Diaphragm, lithium ion secondary battery and electric equipment

By setting a composite layer on the separator of the lithium-ion battery, using the combined action of carbon nanotubes and polydopamine layer, the safety performance problems of lithium-ion batteries under low temperature and high-speed charging conditions are solved, and the safety performance and fast charging capabilities of the battery are significantly improved.

CN119674448AActive Publication Date: 2025-03-21SOUTH CHINA UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411975400.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Lithium-ion batteries have problems with low safety performance under low temperature and large-scale charging conditions, especially the risk of internal short circuit caused by the formation of lithium-ion and lithium dendrites and penetration of the diaphragm.

Method used

A separator is used, which includes a base film and a composite layer, which consists of matrix particles containing carbon nanotubes and a polydopamine layer. The combined action of these layers is significantly improved by the thermal conductivity, flame retardant properties, wetting properties and tensile strength of the separator, thereby inhibiting the formation of lithium and lithium dendrites and preventing them from penetrating the separator.

Benefits of technology

It significantly improves the safety performance of the battery under fast charging and low temperature conditions, reduces the internal short circuit and safety risks caused by the formation of lithium dendrites and penetration of the diaphragm, while maintaining the fast charging capability and mechanical strength of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220978580000091
    Figure BDA0005220978580000091
  • Figure BDA0005220978580000111
    Figure BDA0005220978580000111
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a diaphragm, a lithium ion secondary battery and electric equipment.The diaphragm comprises a base membrane and a composite layer arranged on at least one surface of the base membrane, and the composite layer comprises matrix particles and a polydopamine layer distributed on the surfaces of the matrix particles; the matrix particles comprise an inner core and a silicon dioxide layer distributed on the surface of the inner core, the inner core comprises a carbon nanotube, under the action of the diaphragm, the safety performance of the battery under the conditions of rapid charging and low temperature is greatly improved, the formation of lithium dendrites and the internal short circuit and safety risk caused by the lithium dendrites penetrating through the diaphragm are reduced, and the service life of the battery is prolonged. Therefore, the mechanical strength of the diaphragm is improved, and the fast charging capacity and the safety performance of the battery are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a diaphragm, a lithium-ion secondary battery and an electrical device. Background Art

[0002] The safety of lithium-ion batteries under low temperature and high-rate charging conditions has always been a research focus. Experimental results show that when the lithium ion diffusion rate of the negative electrode cannot meet the demand for fast charging, a large amount of lithium ions will be deposited on the negative electrode surface in the form of metal, thereby increasing the risk of lithium precipitation. As lithium deposition intensifies, the formed lithium dendrites may penetrate the diaphragm, causing direct contact between the positive and negative electrodes, and then causing an internal short circuit. This situation may lead to serious safety accidents such as battery overheating, fire, and even explosion.

[0003] Based on this, how to inhibit lithium precipitation or lithium dendrites and prevent lithium dendrites from penetrating the diaphragm, thereby improving the safety performance of the battery, especially the safety performance under fast charging and low temperature conditions is a technical problem that researchers in this field urgently need to solve in the development of lithium-ion batteries. Summary of the invention

[0004] Therefore, the present application provides a diaphragm, a lithium-ion secondary battery and an electrical device, the purpose of which is to inhibit lithium precipitation or lithium dendrites and prevent lithium dendrites from penetrating the diaphragm, thereby improving the safety performance of the battery, especially the safety performance under fast charging and low temperature conditions.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a diaphragm is provided, which includes a base film and a composite layer arranged on at least one surface of the base film, the composite layer includes base particles and a polydopamine layer distributed on the surface of the base particles, the base particles include an inner core and a silicon dioxide layer distributed on the surface of the inner core, the inner core includes carbon nanotubes, and the silicon dioxide layer includes silicon dioxide.

[0006] Furthermore, the thickness of the silicon dioxide layer is 16-60 nm.

[0007] Furthermore, the thickness of the polydopamine layer is 33-71 nm.

[0008] Furthermore, the thickness of the diaphragm is 8 to 8.5 μm.

[0009] Furthermore, the amount of carbon nanotubes added is 150 to 300 mg.

[0010] Furthermore, the silicon dioxide layer also includes phenolic resin.

[0011] Furthermore, the base film includes one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyethylene (PE), polypropylene (PP), polyvinyl pyrrolidone (PVP), and their derivatives.

[0012] Another aspect of the present application provides a lithium-ion secondary battery comprising any of the above-mentioned separators.

[0013] Another aspect of the present application provides an electric device, comprising any of the above-mentioned lithium-ion secondary batteries, wherein the lithium-ion secondary battery serves as a power supply for the electric device.

[0014] The diaphragm of the present application, a composite layer arranged on the surface of the base film, can not only significantly improve the thermal conductivity of the diaphragm, effectively reduce the temperature difference in the battery cell, thereby reducing the lithium precipitation phenomenon caused by uneven temperature distribution, through the combined effect of the base particles including carbon nanotubes and silicon dioxide distributed on the surface thereof, but also form a flame retardant protective layer on the surface of the diaphragm, significantly improve the flame retardant properties of the diaphragm, and prevent the penetration of lithium dendrites; moreover, it can also significantly improve the wetting properties of the diaphragm, enhance the affinity between the diaphragm and the electrolyte, and contribute to the uniform distribution of the electrolyte, thereby facilitating the uniform distribution of lithium ions on the electrode surface and inhibiting the formation of lithium dendrites; in addition, it can also enhance the tensile strength of the diaphragm, enhance the mechanical stability of the diaphragm, and contribute to improving the diffusion performance of lithium ions, improve the charging and discharging efficiency, so as to enhance the fast charging capability of the battery while effectively resisting the penetration of lithium dendrites. The combined effects of the above greatly improve the safety performance of the battery under fast charging and low temperature conditions, reduce the formation of lithium dendrites and the internal short circuit and safety risks caused by their penetration through the diaphragm, thereby improving both the mechanical strength of the diaphragm and the fast charging capability and safety performance of the battery. DETAILED DESCRIPTION

[0015] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.

[0016] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.

[0017] In the description of this application, "several" means more than one, "more" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, and "above", "below", "within", etc. are understood to include the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0018] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0019] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0020] Existing lithium-ion batteries have the problem of low safety performance under low temperature and high-rate charging conditions. When the lithium ion diffusion rate of the negative electrode cannot meet the demand for fast charging, a large amount of lithium ions will be deposited on the surface of the negative electrode in the form of metal, thereby increasing the risk of lithium precipitation. As lithium deposition intensifies, the formed lithium dendrites may penetrate the diaphragm, causing direct contact between the positive and negative electrodes, and then causing an internal short circuit. This situation may lead to serious safety accidents such as battery overheating, fire, and even explosion. In addition, uneven temperature distribution is also one of the important factors leading to lithium precipitation.

[0021] In order to solve the above technical problems, according to the first aspect of the present application, a diaphragm is provided, which includes a base film and a composite layer arranged on at least one surface of the base film, the composite layer includes base particles and a polydopamine layer distributed on the surface of the base particles, the base particles include an inner core and a silicon dioxide layer distributed on the surface of the inner core, the inner core includes carbon nanotubes, and the silicon dioxide layer includes silicon dioxide.

[0022] The diaphragm of the present application, a composite layer arranged on the surface of the base film, can not only significantly improve the thermal conductivity of the diaphragm, effectively reduce the temperature difference in the battery cell, thereby reducing the lithium precipitation phenomenon caused by uneven temperature distribution, through the combined effect of the base particles including carbon nanotubes and silicon dioxide distributed on the surface thereof, but also form a flame retardant protective layer on the surface of the diaphragm, significantly improve the flame retardant properties of the diaphragm, and prevent the penetration of lithium dendrites; moreover, it can also significantly improve the wetting properties of the diaphragm, enhance the affinity between the diaphragm and the electrolyte, and contribute to the uniform distribution of the electrolyte, thereby facilitating the uniform distribution of lithium ions on the electrode surface and inhibiting the formation of lithium dendrites; in addition, it can also enhance the tensile strength of the diaphragm, enhance the mechanical stability of the diaphragm, and contribute to improving the diffusion performance of lithium ions, improve the charging and discharging efficiency, so as to enhance the fast charging capability of the battery while effectively resisting the penetration of lithium dendrites. The combined effects of the above greatly improve the safety performance of the battery under fast charging and low temperature conditions, reduce the formation of lithium dendrites and the internal short circuit and safety risks caused by their penetration through the diaphragm, thereby improving the mechanical strength of the diaphragm while ensuring the fast charging capability and safety performance of the battery.

[0023] In certain preferred embodiments, the thickness of the silicon dioxide layer is 16 to 60 nm. By controlling the thickness of silicon dioxide within the above range, the diaphragm has good flame retardant properties while not affecting the transmission of lithium ions, so that the battery has better fast charging capability and safety performance. For example, the thickness of the silicon dioxide layer can be 16 nm, 20 nm, 30 nm, 35 nm, 40 nm, 60 nm, etc. or within the range of any of the above values.

[0024] In certain preferred embodiments, the thickness of the polydopamine layer is 33 to 71 nm. By controlling the thickness of the polydopamine layer within the above range, the separator has good wetting properties while not affecting the transmission of lithium ions, so that the battery has better fast charging capability and safety performance. For example, the thickness of the polydopamine layer can be 33 nm, 35 nm, 36 nm, 37 nm, 38 nm, 41 nm, 42 nm, 52 nm, 59 nm, 71 nm, etc. or within the range composed of any of the above values.

[0025] In some preferred embodiments, the silicon dioxide layer also includes a phenol-formaldehyde resin. This resin network can be used as a part of the matrix particles to enhance the mechanical properties and stability of the diaphragm. For example, the phenol-formaldehyde resin can be one or more of catechol-formaldehyde resin, resorcinol-formaldehyde resin, hydroquinone-formaldehyde resin, o-hydroxybenzoic phenol-acetaldehyde resin, m-hydroxybenzoic phenol-formaldehyde resin or p-hydroxybenzoic phenol-furfural resin.

[0026] In some preferred embodiments, the amount of carbon nanotubes added is 150-300 mg. By controlling the amount of carbon nanotubes added within the above range, the internal heat transfer performance of the battery is enhanced and the temperature distribution is more uniform. For example, the amount of carbon nanotubes added can be 150 mg, 180 mg, 200 mg, 230 mg, 250 mg, 280 mg, 300 mg, etc. or within the range of any of the above values.

[0027] Further, the siloxane precursor includes methoxysilane and / or ethoxysilane, and for example, the siloxane precursor includes one or more of tetraethoxysilane, hexaethyldisiloxane, hexamethyldisiloxane, and tetramethyldisiloxane. Wherein, the carboxylated carbon nanotubes can be prepared by conventional methods in the art. For example, the carbon nanotubes are mixed with an oxidant and then heated, wherein the oxidant can be concentrated sulfuric acid and / or concentrated nitric acid.

[0028] In certain preferred embodiments, the base film comprises one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyethylene (PE), polypropylene (PP), polyvinyl pyrrolidone (PVP), and derivatives thereof. The base film has good wettability and thermal stability when in contact with the electrolyte.

[0029] In certain preferred embodiments, the matrix particles of the present application are prepared by reacting carboxylated carbon nanotubes with a siloxane precursor in the presence of a catalyst. Further, the catalyst includes concentrated aqueous ammonia. The weight percentage of concentrated aqueous ammonia can be 25-28%. Further, the siloxane precursor includes methoxysilane and / or ethoxysilane. For example, the siloxane precursor includes one or more of tetraethoxysilane, hexaethyldisiloxane, hexamethyldisiloxane, and tetramethyldisiloxane. Among them, the carboxylated carbon nanotubes can be prepared by conventional methods in the art. For example, the carbon nanotubes are mixed with an oxidant and then heated, wherein the oxidant can be concentrated sulfuric acid and / or concentrated nitric acid.

[0030] In some more preferred embodiments, the preparation method of the matrix particles includes first dissolving the carboxylated carbon nanotubes in a solvent, mixing the alkaline substance, stirring and mixing, and then mixing the phenol, siloxane precursor and aldehyde, and reacting to obtain the matrix particles. Further, after the reaction, centrifugation, washing and drying are also included. Further, the solvent includes an alcohol aqueous solution, for example, an ethanol aqueous solution or a methanol aqueous solution.

[0031] In some more preferred embodiments, the volume ratio of the alkaline substance to the siloxane precursor is 5-15:5-15.

[0032] In certain preferred embodiments, the composite layer is formed by self-polymerization of dopamine on the surface of the base particles. In certain more preferred embodiments, the method for preparing the composite layer includes dispersing the base particles and dopamine in a solvent and reacting them at room temperature. In more preferred embodiments, the solvent includes water or a buffer solution, for example, the solvent can be water, Tris-HCl buffer solution, PBS buffer solution, etc.

[0033] In certain preferred embodiments, the mass ratio of the matrix particles to dopamine is 1-3:1-4.

[0034] In certain preferred embodiments, the reaction further includes centrifugation, washing and drying processes.

[0035] In certain preferred embodiments, the preparation method of the diaphragm of the present application comprises dispersing the matrix particles having the composite layer on the surface in a solvent, filtering through a base membrane, and drying to obtain the diaphragm, wherein the solvent comprises at least one of water, methanol, and ethanol.

[0036] Another aspect of the present application provides a lithium-ion secondary battery comprising any of the above-mentioned separators.

[0037] Another aspect of the present application provides an electric device, comprising any of the above-mentioned lithium-ion secondary batteries, wherein the lithium-ion secondary battery serves as a power supply for the electric device.

[0038] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Specifically, it can include but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0039] Example 1

[0040] This embodiment provides a diaphragm, and the preparation method thereof is as follows:

[0041] (1) Preparation of carboxylated carbon nanotubes: 1.5 g of carbon nanotubes (CNTs) were added to 125 ml of concentrated nitric acid (68% by weight) and stirred continuously at 120° C. for 24 hours. After cooling to room temperature, the mixture was centrifuged and washed with deionized water several times until the solution was neutral. After freeze drying, carboxylated carbon nanotubes were obtained.

[0042] (2) Preparation of matrix particles: 150 mg of carboxylated carbon nanotubes were dissolved in a solution containing 20 ml of deionized water and 200 ml of ethanol, followed by the addition of 9 ml of concentrated ammonia (28% by weight) and stirred for 5 minutes under vigorous stirring. Next, 1.28 g of catechol was added to the mixture and stirred until completely dissolved. Then, 5 ml of tetraethoxysilane (TEOS) and 1.8 ml of formaldehyde were added to the solution in sequence. Next, the solution was stirred at room temperature with a magnetic stirrer for 30 hours. The resulting black solid powder was collected by centrifugation and thoroughly washed with deionized water and ethanol until the solution was neutral. These powders were vacuum dried at 60°C overnight to obtain carbon nanotube particles coated with a silica layer, referred to as CNTs@SiO2 particles.

[0043] (3) Preparation of PDA layer: Prepare 100 mL of Tris-HCl buffer solution (10 mmol / L, pH = 8.5) and disperse 150 mg of CNTs@SiO2 particles in it. Add 150 mg of dopamine to the above solution and stir the reaction at room temperature for 48 hours to promote the self-polymerization of dopamine on the surface of CNTs@SiO2 particles to form a polydopamine (PDA) layer. After the reaction is completed, centrifuge, wash with water 3 times, and then freeze-dry to obtain the matrix particles coated with the PDA layer (referred to as CNTs@SiO2@PDA particles).

[0044] (4) Preparation of membrane: The particles obtained in step (3) were added to 100 mL of 98% ethanol solution by volume. The suspension formed after ultrasonication was filtered through a 25 mm diameter polypropylene (PP) membrane (base membrane) and dried in an oven at 60° C. for 12 hours to form a CNTs@SiO2@PDA composite layer on one side of the PP membrane to prepare a CNTs@SiO2@PDA membrane. The CNTs@SiO2@PDA membrane was then cut into 19 mm diameter discs.

[0045] This embodiment also provides a method for preparing a lithium-ion secondary battery, comprising the following steps:

[0046] (1) Preparation of electrolyte:

[0047] The electrolyte was prepared in a glove box, where the water and oxygen content was less than 1ppm. Lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) was dried in a vacuum oven at 120°C for 10h. First, lithium bis(trifluoromethanesulfonyl)imide (LiFSI) was added to a mixed solvent of dimethoxyethane DME: 1,3-dioxolane DOL = 1:1 (volume ratio) and stirred for 2h to prepare a LiFSI solution with a concentration of 0.5mol / L, and then LiTFSI was added and stirred for 4h to prepare a LiTFSI solution with a concentration of 1mol / L.

[0048] (2) Preparation of positive electrode materials:

[0049] 1) preparing a mixed metal salt solution of Ni, Co, Mn and Al, wherein the total molar concentration of metal ions is 2 mol / L; the molar ratio of Ni, Co, Mn and Al satisfies 8:1:0.5:0.5; preparing a sodium hydroxide strong alkali solution with a molar concentration of 4 mol / L as a precipitant, and preparing an ammonia aqueous solution with a concentration of 3.5 mol / L as a complexing agent;

[0050] 2) adding pure water, the precipitant and the complexing agent into a closed reactor to prepare a bottom liquid, controlling the pH value of the bottom liquid to about 11 by the precipitant, and controlling the ammonia concentration in the bottom liquid to about 0.4 mol / L by the complexing agent; maintaining the temperature of the coprecipitation reaction system at about 50° C. by a circulating water heating jacket.

[0051] 3) Keep the stirring of the reactor on, the speed is about 400rpm, keep the nitrogen flow rate of 20L / min as the protective gas, and add the metal salt mixed solution, the precipitant and the complexing agent in step 1) to the reactor through the dropping funnel for coprecipitation reaction. The pH in the reactor is controlled to be maintained at about 11 during the reaction, the ammonia concentration is 0.6mol / L during the reaction, the reaction temperature is maintained at 50°C, and the speed of the reactor is 400r / min; when the slurry particle size D50 in the reactor grows to 10-18μm, stop the liquid feeding and keep heating and stirring for aging, the aging time is 8 hours, and the aging process is carried out under nitrogen protection.

[0052] 4) The slurry obtained in step 3) is filtered, washed and dried to obtain a high-nickel ternary precursor, the chemical formula of which is Ni 0.8 Co 0.1 Mn 0.5 Al 0.5 (OH)2, D50 is 13.3 μm;

[0053] 5) The above precursor and Li2CO3 were ground and mixed evenly at a molar ratio of 1:0.5, and then placed in a muffle furnace and calcined at 1000°C for 12 hours to obtain LiNi 0.8 Co 0.1 Mn 0.5 Al 0.5 O2 positive electrode material.

[0054] (3) Battery cell production:

[0055] Preparation of positive electrode: LiNi 0.8 Co 0.1 Mn 0.5 Al 0.5The O2 positive electrode material, conductive carbon black and PVDF were evenly mixed in a mass ratio of 8:1:1, and NMP was added to prepare the slurry. The slurry was then evenly coated on the current collector and dried in a vacuum oven at 100°C to obtain the positive electrode sheet.

[0056] Preparation of negative electrode sheet: slurry the negative electrode materials graphite: CMC: conductive carbon black: SBR in a mass ratio of 80:7.5:7.5:5, and evenly apply the slurry on the current collector. Dry the electrode sheet in an oven at 100°C.

[0057] Cell assembly: Assemble the prepared positive electrode sheet, negative electrode sheet, the separator prepared above in this embodiment and the ionic liquid electrolyte into a battery.

[0058] Embodiment 2-3

[0059] The preparation process is basically the same as that of Example 1, except that the amount of tetraethoxysilane used in step (2) during the membrane preparation process is adjusted to 10 ml and 15 ml, respectively, to obtain membranes with different silicon dioxide layer thicknesses.

[0060] Embodiment 4-5

[0061] The preparation process is basically the same as that of Example 1, except that the amount of carboxylated carbon nanotubes in step (1) during the membrane preparation process is adjusted to 200 mg and 300 mg respectively, thereby obtaining membranes with different silicon dioxide layer thicknesses.

[0062] Embodiments 6 to 8

[0063] The preparation process is basically the same as that of Example 1, except that the amount of dopamine in step (3) during the membrane preparation process is adjusted to 200 mg, 300 mg, and 400 mg, respectively, to obtain membranes with different polydopamine layer thicknesses.

[0064] Embodiments 9-10

[0065] The preparation process is basically the same as that of Example 1, except that the type of base film in step (3) of the membrane preparation process is regulated to obtain different membranes.

[0066] Comparative Example 1

[0067] The preparation process is basically the same as that of Example 1, except that step (2) is omitted in the membrane preparation process, and step (3) uses the same mass of carboxylated carbon nanotubes to replace the CNTs@SiO2 particles in Example 1.

[0068] Comparative Example 2

[0069] The preparation process is basically the same as that of Example 1, except that step (3) is omitted in the membrane preparation process, and step (4) uses CNTs@SiO2 particles of the same mass prepared in step (2) to replace the particles prepared in step (3) of Example 1.

[0070] Comparative Example 3

[0071] The preparation process is basically the same as that of Example 1, except that steps (2) and (3) are omitted in the membrane preparation process, and step (4) uses the same mass of carboxylated carbon nanotubes to replace the particles prepared in step (3) of Example 1.

[0072] Comparative Example 4

[0073] The preparation process is basically the same as that of Example 1, except that the diaphragm uses a PP film.

[0074] Table 1 Physical parameters of the diaphragms of various embodiments and comparative examples

[0075]

[0076] " / " means it does not exist

[0077] 1. Determination of physical parameters:

[0078] 1)Thickness of silicon dioxide layer

[0079] The test method is as follows: 1 mg of the matrix particles prepared in each embodiment and comparative example 2 is dispersed in 2 ml of ethanol, ultrasonicated for 5 minutes, and the dispersed solution is dropped on a special copper mesh, which is covered with a thin film to support the sample. The solvent is allowed to evaporate, so that the sample is evenly distributed on the copper mesh, and TEM is taken. The TEM image can be quantitatively analyzed using image analysis software, and the shell thickness of the core-shell structure can be obtained through statistical analysis.

[0080] 2) Thickness of polydopamine layer

[0081] The test method is as follows: 1 mg of the PDA layer-coated matrix particles prepared in each embodiment and comparative example 1 is dispersed in 2 ml of ethanol, ultrasonicated for 5 minutes, and the dispersed solution is dropped on a special copper mesh, which is covered with a thin film to support the sample. The solvent is allowed to evaporate, so that the sample is evenly distributed on the copper mesh, and TEM is taken. The TEM image can be quantitatively analyzed using image analysis software, and the thickness of the PDA layer can be obtained through statistical analysis.

[0082] 2. Safety performance

[0083] (1)Puncture resistance test

[0084] The diaphragms prepared in the embodiments and comparative examples were cut into strips and mounted on the fixed clamp ring of the diaphragm puncture tensile machine. Then, a steel needle with a diameter of 1.0 mm and a radius of 0.5 mm at the top was used to puncture the strips at a speed of (50±5) mm / min, and the maximum load of the steel needle penetrating the test piece was read. The test generally measured 3 points, and the arithmetic average was taken. The number of test pieces was more than 5.

[0085] (2) Tear resistance test

[0086] According to GB / T 1040.3-2006, the tensile strength test of battery separators requires the use of a type 2 specimen with a width of (15±0.1) mm. During the test, an MTL (PC) tensile testing machine was used. The initial distance between the clamps should be set to (100±5) mm, and the test speed should be controlled at (250±10) mm / min.

[0087] The technical parameters of the MTL (PC) tensile testing machine include a test range of 0-500N (other ranges are optional), a measurement accuracy of 0.3, a stroke of 1000mm, a test speed of 0.5-500mm / min stepless speed change, and a displacement accuracy of 0.01mm. The tensile testing machine can measure the ratio of the maximum force that the diaphragm can withstand before breaking under pure tensile force to the cross-sectional area of ​​the tested diaphragm. This ratio is the tensile strength.

[0088] 3. Battery fast charging performance test:

[0089] The lithium-ion secondary batteries prepared in the embodiments and comparative examples were tested for fast charging performance, and the specific method is as follows: Under room temperature, the battery cell with SOC=0% state of charge was charged to 4.5V at a current density of 0.33C, and the capacity at this time was C1. Under room temperature, the same battery cell with SOC=0% state of charge was charged to 4.5V at a current density of 5C, and the capacity at this time was C2. The test index of the charging rate performance is the capacity retention rate, and the fast charging capacity retention rate = C2 / C1*100%.

[0090] The test results are shown in Table 2.

[0091] Table 2 Battery rate performance and fast charging performance test results

[0092]

[0093] It can be seen from the above table that, compared with comparative examples 1 to 4, the diaphragms prepared in the embodiments of the present application can not only significantly improve the battery safety performance, but also maintain a relatively high fast charging performance of the battery.

[0094] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.

Claims

1. A diaphragm, characterized in that: The diaphragm includes a base film and a composite layer arranged on at least one surface of the base film, the composite layer includes base particles and a polydopamine layer distributed on the surface of the base particles, the base particles include an inner core and a silicon dioxide layer distributed on the surface of the inner core, the inner core includes carbon nanotubes, and the silicon dioxide layer includes silicon dioxide.

2. The diaphragm according to claim 1, characterized in that The thickness of the silicon dioxide layer is 16-60 nm.

3. The diaphragm according to claim 1, characterized in that The thickness of the polydopamine layer is 33-71 nm.

4. The diaphragm according to claim 1, characterized in that The thickness of the separator is 8 to 8.5 μm.

5. The diaphragm according to claim 1, characterized in that The added amount of the carbon nanotubes is 150 to 300 mg.

6. The diaphragm according to claim 1, characterized in that The silicon dioxide layer also includes a phenolic resin.

7. The diaphragm according to claim 1, characterized in that The base film includes one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyethylene (PE), polypropylene (PP), polyvinyl pyrrolidone (PVP), and derivatives thereof.

8. A lithium ion secondary battery, characterized in that: The invention comprises the diaphragm according to any one of claims 1 to 7.

9. An electrical device, characterized in that: It comprises the lithium ion secondary battery as claimed in claim 8, and the lithium ion secondary battery is used as a power supply for the electrical equipment.

Citation Information

Patent Citations

  • Functionalized polyolefin composite diaphragm and preparation method and application thereof

    CN111725466A

  • A separator, the manufacturing method thereof, and electrochemical device containing the same

    KR1020130099463A

  • Separator Having Excellent Thermal Conductivity and Electrochemical Element Using the Same

    US20220216569A1

  • Ceramic microsphere, diaphragm including ceramic microsphere and lithium ion battery including diaphragm

    US20220278421A1

  • Heat-conducting lithium ion separator and preparation method therefor

    WO2023098044A1